Progress in Elucidating the Mechanism of Selenium in Mitigating Heavy Metal Stress in Crop Plants - Shuqing Jia; Qing Guan; Yulong Niu; Ye Wang; Linling Li; Hua Cheng (Agriculture)
In the context of rapid industrialization and agricultural modernization, the issue of heavy metal (HM) pollution has surfaced as a critical concern, posing a substantial threat to human health and having a profound impact on agricultural cultivation. Selenium (Se), a beneficial micronutrient for crop growth and development, exerts numerous beneficial effects, including facilitating photosynthesis, enhancing physiological attributes, improving nutritional quality, strengthening antioxidant systems, and modulating the expression of stress-responsive genes. Notably, Se plays a pivotal role in alleviating HM stress in crops and effectively mitigating the accumulation of HMs in edible plant parts. This study investigates the physiological and molecular mechanisms underlying Se’s capacity to alleviate HM stress in crops. Additionally, we discuss the application of Se-enriched fertilizers in agricultural practices, as well as the influence of environmental factors on their effectiveness. Our objective is to contribute to sustainable agricultural development and the production of safe, high-quality agricultural products, thereby providing valuable insights for the development of Se-functional industries and guiding agricultural practices in regions affected by HM pollution.